Sediment contamination alters the submersed macrophyte Vallisneria natans and root-associated microbiome profiles during phytoremediation - Yan, Zaisheng; Wei, Haoming; Wang, Hongyang; Ye, Huaxiang (Ecotoxicology and environmental safety, 2024)
The submerged plant Vallisneria natans plays an important role in the remediation of polycyclic aromatic hydrocarbon (PAH)-contaminated sediments. In this study, V. natans and sediments were collected from different V. natans natural vegetation zones, and sediment mesocosms were set up for phytoremediation tests. In addition, commercial-grade V. natans were obtained from the Fish-Bird-Flower market for comparison with phytoremediation. Phytoremediation using V. natans from natural growth significantly increased the degradation of PAHs in Dashui Harbor (0.0148±0.0015 d−1) and Taihu Lake bay sediments (0.0082±0.0010 d−1) but not in commercial-grade V. natans. Transplanted V. natans from natural growth had a significant (p=0.002) effect on PAH degradation, especially in highly PAH-contaminated sedimentary environments. The distinct bacterial communities were strongly affected by sediment type and V. natans type, which contributed to different phytoremediation patterns. Less complex but more stable microbial co-occurrence networks play key roles in improving PAH phytoremediation potential. In addition, V. natans from natural growth in highly PAH-contaminated sediment could adapt to PAH stress by exuding tryptophan metabolites to assemble health-promoting microbiomes. This study provides novel evidence that initial microbial and physicochemical characteristics of sediment and submerged plant types should be considered in the use of bioremediation management strategies for organic pollutant-contaminated sediments. [Display omitted] •Sediment contamination altered V. natans and root-associated microbiomes profiles.•Bacterial communities were strongly affected by sediment type and V. natans type.•Commercial-grade V. natans introduction could not adapt to PAH highly stress.•A less complex but more stable microbial networks played key roles in phytoremediation.•V. natans changed exudation chemistry to assemble health-promoting microbiomes.